Human Resources Management in the Judicial Administration in the Context of Digitalization - Managerial and Legal Aspects - Dimitrova, Darina; Dimitrova, Diana; Koleva, Velina (Research Papers, 2024)
The administration of the judiciary is an integral part of the structure of the state administration, but human resource management specifically in the judicial administration is still an understudied area. The scientific objective of this work is to examine the main managerial and legal aspects of human resources management in the judicial administration in the conditions of digitalization. Specific research approaches and methods are applied to achieve the formulated objective. In the theoretical-methodological plan, a systematic approach, a method of analysis and synthesis, an interdisciplinary approach, a descriptive method, etc. are used. Along with these, we use survey research, in-depth interviews, participation in discussions, and content analysis of documents in an empirical way. The approaches applied in the overall study are those of induction and deduction. As a result of the complex analysis, conclusions and generalizations are drawn and solutions are proposed to improve the work of the judiciary administration.
Keywords: Judicial administration; Human resources management; Digitization